IMPROVING THE STUDENTS’ ABILITY IN WRITING REPORT GENRE THROUGH MIND MAPPING AT JUNIOR HIGH SCHOOLS IN SOUTH SUMATERA, INDONESIA - Riswanto, . (PEOPLE: International Journal of Social Sciences, 2016)
This research was conducted to improve the IX-5 grade students’ ability in writing report genre by using mind-mapping strategy. The population of this research were the IX-5 students of SMP Negeri 17 Palembang. The total samples were 43 students. In taking the data, the researcher used classical approach which was taking in three ways, observation, questionnaire and test. In doing the observation data the researcher was helped by two English teachers to know the students’ improvement from cycle to cycle. The result of the research showed that there is good impact to the students’ achievement and ability in writing report genre through mind-mapping technique. In conclusion, mind-mapping technique is a suitable strategy to improve the students’ ability in writing report genre.